New Form Architecture Within Modern Heritage: Modernization Factors in Transportation, Industry, and Construction Materials - Masyiana Arifah Alfia Riza; Wijayanti Wijayanti (Sinektika: Jurnal Arsitektur, 2026)
Modern heritage is understood as a legacy of the past that embodies ways of thinking adapted to contemporary demands. It represents a new type of architecture that emerged between the nineteenth and twentieth centuries, encompassing architecture, urban planning, and landscape design, and is characterized by new modes of thought in which past and future converge, enabling collaboration between designers and conservators. Modern architecture constitutes a new symbolic form that directly expresses contemporary reality rather than continuously reproducing historical references. The characteristics and paradigms developed during the modern period have become an important part of global architectural development, contributing new knowledge and perspectives that give rise to what is referred to as new form architecture. This study aims to provide a new theoretical contribution to the concept of new form architecture within modern heritage, using a qualitative approach with descriptive content analysis. The findings show that modern heritage produces new form architecture derived from nineteenth-century modernism, introducing new building typologies as a result of the Industrial Revolution, which generated new technologies to support nineteenth-century societal activities. The emergence of these typologies is closely related to industrial developments in transportation, industry, and construction materials.